Association of admission hyperglycemia and all-cause mortality in acute myocardial infarction with percutaneous coronary intervention: A dose–response meta-analysis - Cheng, Shao-Yong; Wang, Hao; Lin, Shi-Hua; Wen, Jin-Hui; Ma, Ling-Ling; Dai, Xiao-Ce (Frontiers in Cardiovascular Medicine, 2022)
Objective The aims are to evaluate the associations between admission hyperglycemia and the risk of all-cause mortality in acute myocardial infarction patients with or without diabetes, to find optimal admission glucose intervention cut-offs, and to clarify the shape of the dose-response relations. Method Medline/PubMed, EMBASE were searched from inception to 1st April 2022. Cohort studies reporting estimates of all-cause mortality risk in admission hyperglycemia patients with acute myocardial infarction were included. The outcomes of interest include mortality, major adverse cardiac events. A random effect dose-response meta-analysis was conducted to access linear trend estimations. A one-stage linear mixed effects meta-analysis was used for estimating dose-response curves. Relative risks and 95% confidence intervals were pooled using a random-effects model. Results Of 1,222 studies screened, 47 full texts were fully reviewed for eligibility. The final analyses consisted of 23 cohort studies with 47,177 participants. In short-term follow-up, admission hyperglycemia was associated with an increased risk of all-cause mortality (relative risk 3.12, 95% confidence interval 2.42 to 4.02), major adverse cardiac events (2.34, 1.77 to 3.09). In long-term follow-up, admission hyperglycemia was associated with an increased risk of all-cause mortality (1.97, 1.61 to 2.41), major adverse cardiac events (1.95, 1.21 to 3.14). A linear dose-response association was found between admission hyperglycemia and the risk of all-cause mortality in patients with or without diabetes. Conclusions Admission hyperglycemia was significantly associated with a higher all-cause mortality risk and rates of major adverse cardiac events. However, the association between admission hyperglycemia and long-term mortality risk needs to be determined with caution. Compared with current guidelines recommendations, a lower intervention cut-off and more stringent targets for admission hyperglycemia may be appropriate.